Disaster Risk Analysis to Support the Development of Regional Spatial Plan of Tasikmalaya Regency, Indonesia - Wiwin Winarti (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2018)
Tasikmalaya Regency is one of the regencies on the West Java Province that is vulnerable to disaster and currently in the second position at national level. Based on data from BPBD (Regional Disaster Management Agency) of Tasikmalaya Regency, from January to June 2016, total disaster was 243 events and 64% landslide disaster, with total loss of IDR 19.5 billion. Therefore, multi-disaster risk mapping is necessary, as a form of mitigation effort. This multi-disaster mapping was arranged with steps as follows: analysis and mapping of vulnerability or susceptibility, capacity and risk of each disaster, based with Geographic Information System (GIS) with Arc Map 10.3 software, then being combined (overlay). The susceptibility and capacity levels used the parameters as according to Regulation of Chief of BNPB (Badan Nasional Penanggulangan Bencana – Indonesian National Board for Disaster Management) No. 02 Year 2012, which are: social susceptibility, economy susceptibility, physical susceptibility and environmental susceptibility. Study of landslide, flood, and earthquake disasters risks were classified according to BNPB Chief Regulation No. 02 Year 2012 into 3 (three) multi-disaster risk classes with Natural Breaks (Jenks) method, which resulted into: low risk class (57.01%), medium risk class (35.08%), and high risk class (7.92%). Based on the study, it is known that the region with classification of high risk to disaster needed to be rearranged in the spatial pattern planning, as a revision material for the Land Use Plan (Rencana Tata Ruang Wilayah – RTRW) of Tasikmalaya Regency in 2011-2031.